2010
DOI: 10.1002/jcp.22355
|View full text |Cite
|
Sign up to set email alerts
|

Altered intracellular calcium fluxes in pancreatic cancer induced diabetes mellitus: Relevance of the S100A8 N‐terminal peptide (NT‐S100A8)

Abstract: After isolating NT-S100A8 from pancreatic cancer (PC) tissue of diabetic patients, we verified whether this peptide alters PC cell growth and invasion and/or insulin release and [Ca(2+)](i) oscillations of insulin secreting cells and/or insulin signaling. BxPC3, Capan1, MiaPaCa2, Panc1 (PC cell lines) cell growth, and invasion were assessed in the absence or presence of 50, 200, and 500 nM NT-S100A8. In NT-S100A8 stimulated β-TC6 (insulinoma cell line) culture medium, insulin and [Ca(2+)] were measured at 2, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…In a previous study we demonstrated that PDAC tissue is enriched by the biologically active N-terminal 14 aa fragment of S100A8 (NT-S100A8) [34]. In this study, in order to further exploit tumor stoma interactions, we first verified whether tumor cells release soluble mediators able to fragment the S100A8 protein.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In a previous study we demonstrated that PDAC tissue is enriched by the biologically active N-terminal 14 aa fragment of S100A8 (NT-S100A8) [34]. In this study, in order to further exploit tumor stoma interactions, we first verified whether tumor cells release soluble mediators able to fragment the S100A8 protein.…”
Section: Discussionmentioning
confidence: 89%
“…The levels of calcium binding proteins S100A8 and S100A9 increase in cancer, including PDAC; although mainly expressed by tumor-infiltrating inflammatory cells, they may also be expressed by PDAC cells [31,34]. These proteins are directly involved in piloting metastases by the ligation of TLR4 and RAGE receptors [29,30,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Reportedly, more than 80% of patients with PaCa have frank DM or a reduced glucose tolerance, 6,7 and this frequently encountered metabolic alteration is believed to be caused by PaCaderived diabetogenic products, including the low molecular weight diabetogenic S100A8 fragment previously isolated in our laboratory. 8 These observations have prompted some investigators to suggest that patients presenting with new-onset DM should undergo screening for PaCa. 9Y11 However, the appropriate serum marker for screening in patients with diabetes has yet to be identified, since CA 19-9 is not feasible for this purpose, because it is limited in sensitivity and, in patients with diabetes, it might increase in the event of diabetic complications.…”
mentioning
confidence: 99%